Enhancing Emotional Intelligence through Role-Play Activities in Early Childhood Education - Citra Dewi (Pt. Anagata Sembagi Education, 2025)
This study examines how role-play activities enhance emotional intelligence in early childhood education through a systematic literature review of 33 empirical and conceptual publications. Findings demonstrate that role-play develops emotional awareness, empathy, emotional regulation, social collaboration, and executive functioning through experiential and imaginative interactions. Children learn to understand and manage emotions by embodying diverse social characters, negotiating group dynamics, and engaging in emotionally rich scenarios supported by teacher facilitation. Sustainability of role-play requires structural support including teacher professional development, leadership commitment, parental involvement, resource management, and cultural contextualization to ensure consistent emotional learning rather than occasional dramatic play. This review contributes by synthesizing mechanisms and pedagogical components that make role-play a holistic and sustainable approach to enhancing emotional intelligence in early childhood education.